2021
DOI: 10.1002/advs.202004831
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Child Gut Microbiota Enter into Bone to Preserve Bone Mass and Strength

Abstract: Recently, the gut microbiota (GM) has been shown to be a regulator of bone homeostasis and the mechanisms by which GM modulates bone mass are still being investigated. Here, it is found that colonization with GM from children (CGM) but not from the elderly (EGM) prevents decreases in bone mass and bone strength in conventionally raised, ovariectomy (OVX)‐induced osteoporotic mice. 16S rRNA gene sequencing reveals that CGM reverses the OVX‐induced reduction of Akkermansia muciniphila (Akk). Direct replenishment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 86 publications
4
90
0
1
Order By: Relevance
“…22,41,42 Moreover, our recent work revealed that Akk-EVs recapitulate the effects of Akk on promoting bone metabolism balance and protecting against osteoporosis. 23 In this study, we found that these EVs could elicit a protective effect via reducing the tumor burden in PCa mice.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…22,41,42 Moreover, our recent work revealed that Akk-EVs recapitulate the effects of Akk on promoting bone metabolism balance and protecting against osteoporosis. 23 In this study, we found that these EVs could elicit a protective effect via reducing the tumor burden in PCa mice.…”
Section: Discussionmentioning
confidence: 60%
“…The medium was then concentrated with Amicon Ultra-15 Centrifugal Filter (100 kDa; Millipore), and the EV pellet was obtained by serial gradient centrifugation with OptiPrep™ solution (60% w/v iodixanol; Sigma-Aldrich) at 100,000 × g for 18 h at 4 °C. 23 Collected EVs were resuspended in PBS and filtered through a 0.22 μm filter to avoid any contamination. After total protein concentration quantification, EVs were stored at −80 °C for further study.…”
Section: Isolation Of Akk-evsmentioning
confidence: 99%
“…Proteobacteria was reported to be the main phylum of pathogenic bacteria, which promoted the production of excessive pro-inflammatory cytokines and related to IBD pathogenesis (24,42). Akkermansia was a confirmed probiotic with anti-inflammatory effect by improving neutrophil infiltration and alleviating intestinal inflammation (44)(45)(46). Bifidobacteria could exert an anti-inflammatory effect through induction of intestinal IL-10 and protect from Th1driven inflammation (42).…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs, the main metabolites in the colon generated from bacterial fermentation of dietary fibres, increased bone mineral density by inhibiting osteoclast differentiation and bone resorption (Lucas et al., 2018 ). A recent study showed that EVs derived from gut microbiota enriched in Akkermansia muciniphila from healthy children showed suppressive effects on osteoclastogenesis and protective effects against osteoporosis in ovariectomized mice (Liu et al., 2021 ). A. muciniphila is a promising probiotic that also suppresses P. gingivalis ‐induced osteoclast activation and bone resorption (Huck et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%